History and impact of the scientific literature of the Department of Madre de Dios, Peru - A. Pitman, Nigel C. (2008)
Books, articles, government documents, and other written accounts of tropical biology and conservation reach a tiny fraction of their potential audience. Some texts are inaccessible because of the language in which they are written. Others are only available to subscribers of developed-world journals, or distributed narrowly within tropical countries. To examine this dysfunction in the tropical literature—and what it means for conservation—we spent a year trying to compile everything ever written on the biology and conservation of the department of Madre de Dios, Peru, in southwestern Amazonia. Our search of libraries, databases, and existing bibliographies uncovered 2202 texts totaling roughly 80000 pages. Texts date from 1553 to 2004, but 93% were written after 1970. Since that year the publication rate has increased steadily from fewer than ten texts per year to nearly three texts per week in 2004. Roughly half of the Madre de Dios bibliography is accounted for by Spanish-language texts written by Peruvian authors and mostly inaccessible outside Peru; most of the remainder are English-language texts written by foreign authors and largely inaccessible in Peru. Foreign authors tended to write about ecological studies with limited relevance to on-the-ground conservation challenges, while Peruvian authors were more likely to make specific management recommendations. In the list of most written-about topics, sustainable use of natural resources ranks third behind ecology and animal behavior. We conclude with some recommendations for converting the tropical literature to a more open and efficient resource for science and conservation